Penggunaan Kromium Organik dari Beberapa Jenis Fungi terhadap Aktivitas Fermentasi Rumen Secara in Vitro - W D Astuti; T Sutardi; D Evvyernie; T Toharmat (Faculty of Animal Science, Bogor Agricultural University, 2006)
Chromium appears to be an essential trace element since 1959, but its effect on ruminal microbes is not clear yet. This experiment was conducted to study the effects of organic chromium supplementation on rumen fermentation activity. An in vitro technique was held using randomized block design with 13 treatments and 3 replications. There were four kinds of organic Cr used, produced with four different species of fungi as carriers. Fungi used as carriers were Saccharomyces cerevisiae, Aspergillus oryzae, Rhizophus oryzae and